An Analysis of Vocational School Students’ Need during Online Learning in Pandemic Covid-19 Era - Yan Imam Santoso; Prasetyawan Aji Sugiharto (Universitas Muhammadiyah Kalimantan Timur, 2022)
Online learning is the alternative teaching technique in this situation. Combining technology in learning English may be not weird for some teachers. However, some teachers are made confused by technology because of their knowledge. The pandemic of covid-19 thrust on the teacher for utilizing the technology in teaching and learning. The teacher has faced two conditions where they are not only learning about technology but, also should develop their materials. In developing the material for vocational school, the teachers have to know the need of their students. This research is aimed to analyze the students’ needs in teaching and learning which are conducted by online learning. The material, method, media, or technique in teaching and learning should be paid attention to. This research is descriptive qualitative research with use population vocational school in Purworejo. The sample of this research is tenth graders of SMK N 7 Purworejo and SMK Muhammadiyah Purworejo. The collecting data technique is an observation of the document and interview with the students and teachers. The result of this research is the materials should be developed/modified based on the major of their students. Speaking, pronunciation, and vocabulary are needed to emphasize online learning. The teacher must improve their media of teaching by using interactive media. So the teachers have to be more creative in using technology. The technique, method, or approach should be adaptable with the material of students’ needs, learning media, and textbook that is used. In conclusion, the teacher was hoped that they know how to use the technology, develop the materials based on their major, and improvisation of teaching and learning techniques, methods, and approaches.